Complementary Split Ring Resonator Based Triple Band Microstrip Antenna for WLAN/WiMAX Applications - Ali, Wael; Hamad, Ehab; Bassiuny, Mohamed; Hamdallah, Mohamed (Společnost pro radioelektronické inženýrství, 2017)
A new simple design of a triple-band microstrip antenna using metamaterial concept is presented in this paper. Multi-unit cell was the key of the multi resonance response that was obtained by etching two circular and one rectangular split ring resonator (SRR) unit cells in the ground plane of a conventional patch operating at 3.56 GHz .The circular unit cells are resonating at 5.6 GHz for the upper band of Wi-MAX, while the rectangular cell is designed to produce a resonance at 2.45 GHz for the lower band of WLAN. WiMAX's/WLAN's operating bands are covered by the triple resonances which are achieved by the proposed antenna with quite enhanced performance. A detailed parametric study of the placement for the metamaterial unit cells is introduced and the most suitable positions are chosen to be the place of the unit cells for enhanced performance. A good consistency between simulation and measurement confirms the ability of the proposed antenna to achieve an improved gain at the three different frequencies.
Keywords: Metamaterial; metasurface; multi band antennas; CSRR; split ring resonators